ADAPTATION NOVACO ANGER SCALE (NAS) IN INDONESIA AS AN PSYCHOMETRIC INSTRUMENT TO MEASURE THE EMOTION OF ANGER - Wahyu Nurhayati (Widyariset, 2012)
This study aims to develop and validate the Novaco Anger Scale (NAS) in Indonesia. NAS is a psychometric instrument to measure the emotion of anger that focuses on the theoretical dimension of the concept of emotional upset. NAS is designed to measure aspects of cognitive, physiological, impulsive behaviour respons, and angry management. NAS had previously been adapted in Sweden. Sampel used is 29 students and 67 student of the University of Persada Indonesia Jakarta (N = 96). Data analysis conducted by factor analysis, analysis of construct validity and reliability test. The results showed that the NAS adaptation has good validity and reliability.